2012
DOI: 10.1007/s40037-012-0033-0
|View full text |Cite
|
Sign up to set email alerts
|

Crossword puzzles: self-learning tool in pharmacology

Abstract: Students of the second professional MBBS course of the Indian medical curriculum (II MBBS) perceive pharmacology as a ‘Volatile Subject’ because they often find it difficult to remember and recall drug names. We evaluated the usefulness of crossword puzzles as a self-learning tool to help pharmacology students to remember drug names. We also measured the students’ satisfaction with this learning method. This was an open-label randomized, two-arm intervention study, conducted with II MBBS students (n = 70), ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 19 publications
1
37
1
2
Order By: Relevance
“…Only one previous study in education of health professionals used a randomized control design and pretest-posttest analysis to determine the effectiveness of crossword puzzles for learning drug names. 18 Our results are similar to the findings of that study: pre-test scores were similar in both intervention and control group, with a subsequent increase in the post-test scores in both groups, although the average score was significantly higher in the intervention group. This supports the view that the use of crossword puzzles during a defined learning period is more effective than just memorization of the terms and their definitions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only one previous study in education of health professionals used a randomized control design and pretest-posttest analysis to determine the effectiveness of crossword puzzles for learning drug names. 18 Our results are similar to the findings of that study: pre-test scores were similar in both intervention and control group, with a subsequent increase in the post-test scores in both groups, although the average score was significantly higher in the intervention group. This supports the view that the use of crossword puzzles during a defined learning period is more effective than just memorization of the terms and their definitions.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, previous research has shown that puzzles are effective both as an in-class activity 6-8, 12, 19, 23 and as a self-learning tool. 18 The participants of this study (including those not exposed to the puzzles in the intervention) said that they were likely to use the crossword puzzles if they were just provided as a self-learning tool.…”
Section: Discussionmentioning
confidence: 96%
“…Minimum samples of 70 students were targeted based upon earlier study. 12 A total of 78 second year MBBS students participated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…3,[11][12][13][14][15][16][17][18][19][20][21][22][23] Studies conducted in limited subjects in medicine have documented promising results and substantiate the usability of this technique as a modern pedagogic tool. 3,12,19,[22][23][24] Pharmacology is an important subject to develop rationale behind therapeutics in disease management. However, it is perceived to be dry and volatile by students due to extensive core content, information overload, difficult to remember drug names and recall the same as well the concepts in the subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation